Control of Iatrogenic urogenital fistula in developing country - Sharma, Suman (Nepal Journal of Obstetrics and Gynaecology, 2018)
Urogenital fistula is one major health problem of developing countries. It is an abnormal communication between genital tract (Vagina, Cervix and Uterus) and urinary tract (Bladder, Urethra and Ureter) secondary to obstetrical trauma or iatrogenic insult, causing continuous urinary leakage. The previous studies shows obstructed labor as main cause of urogenital fistula but recently received an increase number of patients after gynaecological and obstetrical surgeries mainly hysterectomies and C -section. Iatrogenic urogenital fistula is not yet recorded as frequently as in some region such as southern Asia, but is becoming an issue with significant concern for treatment and prevention.Iatrogenic urogenital fistula is an indicator of the health system failing to provide good and quality health care system. Iatrogenic fistula which is induced inadvertently by a surgeons or diagnostic procedure. There are several regions for iatrogenic urogenital fistula like unsafe surgeries, rising in C-section and hysterectomy surgeries. Iatrogenic urogenital fistula commonly occurs in emergency procedures conducted by the resident/junior registrars or lack of proper surgical training of surgeons performing these surgeries . Sometime it may be due to abnormal surgical anatomy . Few things we can do to reduce or minimize Iatrogenic urogenital fistula . Firstly safe surgical practices for C-section, hysterectomy and ruptured uterus repair. We must improve training, establish standardized surgical ,anesthesia and obstetric criteria. At least few months rotational training in urology should be mandatory for resident in obstetrics and gynaecology to deal with common complication of bladder, urethra and ureter encounter during gynaecological and obstetrical surgeries. Secondly we must reduce unnecessary surgeries such as C-section and hysterectomy. Finally we must expand access to basic maternal health care. All women have the rights to family planning to space desired birth and quality midwifery services to reduce unnecessary C-section and promote optimal birth outcome.